TEACHING MOTIVATION IN RELATION TO CLASSROOM MANAGEMENT PRACTICES AMONG PUBLIC ELEMENTARY SCHOOL TEACHERS OF KAWAYAN DISTRICT-1 KAWAYAN BILIRAN PROVINCE - Ms. Margaret O. Flores; Dr. Glenn R. Andrin; Dr. Mario Ramil Pepito; Ms. Maria Teresa Lupian (European Journal of Humanities and Educational Advancements, 2023)
This study determined the correlation between teachers’ motivation in relation to classroom management practices among public elementary school teachers in the district of Kawayan, Biliran Province. Descriptive survey method was employed as Best and Kahn (1999) confirmed for its relevancy. Descriptive survey helps to describe and interpret the trend of event that exist now and exist in the past and that influence on the present situation.Self-Actualization needs garnered the highest mean while Physiological Needs garnered the lowest mean. Maximizing structure and predictability in the classroom got the highest mean score while Using a continuum of strategies to acknowledge appropriate behavior obtained the lowest mean score. Of the five variables of the respondents’ profile, only the teachers’ highest educational attainment has a significant relationship to their motivation. It is then expedient to say that teacher’s educational attainment has a significant degree of relation to motivation. Only sex has a significant relationship to the classroom management practices. The results led to the rejection of the null hypothesis. It can then be said that the sex profile of the teacher respondents has a significant degree of relationship to that of their classroom management practices. There is a significant degree of variances between and among Physiological, Security, Social and Self-Actualization Needs. A closer look revealed that self-actualization as the prime motivator among the respondents while physiological needs to be the least motivator.The results revealed that the ten dimensions of the classroom management representatives differ from one another